ANALYZE OF FACTORS AFFECTING GENERATION Z'S INVESTMENT INTEREST IN THE CAPITAL MARKET - Wulandari, Vina Yuliantika; Supeni, Retno Endah; Hafidzi, Achmad Hasan (Univesitas Muhammadiyah Tangerang, 2025)
The results of this research are also in line with the researcher who is carried out by factors that affect the desire of generation Z, especially KSPM students at universities in Jember Regency, to invest in the capital market. Generation Z as a digital generation that is familiar with technology has special characteristics that need to be understood in the context of investment behavior and researchers are more focused on choosing KSPM as the object of research because KSPM is an extension of the capital market in general for students. The population of this study includes generation Z, especially students who take part in KSPM at the University of Jember Regency which totals 152 students who were taken as research samples using non-probability sampling techniques, data processing was analyzed by multiple linear regression, with hypothesis testing using t-test. The researcher's research shows that the impact of investment knowledge, minimum capital, risk preferences and social media influencers significantly affects investment interest.